Measurement, Reporting and Verification (MRV) Platform for Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
As documented by World Bank and the government of Uruguay, a website platform with specific guidance, data and tools is an effective means for scaling out action. Climate change reporting officers for the governments of Costa Rica, Mongolia and Senegal have indicated by email that they find the platform useful.